Até que a morte nos separe: violência entre parceiros íntimos com mulheres indígenas dos povos Atikum e Pankará - Sá Neta, Maria das Graças Gonçalves Freire de (Universidade Federal de São Carlos, 2025)
Intimate partner violence (IPV) is recognized as a global public health issue that affects approximately 30% of women worldwide. In particular, for Indigenous women, the literature is scarce and their experiences are often rendered invisible. This study aimed to investigate the variables that either inhibited or contributed to the breaking of the cycle of IPV among Indigenous women from the Atikum and Pankará peoples. Six women participated (three from the Atikum and three from the Pankará ethnic groups), all of whom were victims of IPV and had ended their relationships with their partners. In-person individual interviews were conducted with each of them. The data were transcribed and analyzed using thematic content analysis. The results indicated that the escalation of violence and the partner's use of alcohol and drugs were driving factors, while the normalization of violence and fear of social judgment were inhibiting factors in ending the relationship. Children acted as both motivators and barriers. Addressing IPV in Indigenous contexts requires an approach that is sensitive to the cultural, spiritual, and collective specificities of these women, breaking away from the universalizing logic of traditional interventions.
Until death do us part: intimate partner violence against indigenous women of the Atikum and Pankará peoples
Keywords: Violência por parceiro íntimo; Mulheres; Indigenas; Intimate partner violence; Women; Indigenous people; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA